An empirical study of portfolio management and Kanban in agile and lean software companies. Issue 6 (2nd November 2016) - Ahmad, Muhammad Ovais; Lwakatare, Lucy Ellen; Kuvaja, Pasi; Oivo, Markku; Markkula, Jouni
Abstract: Traditional portfolio management tools and methods are challenging for software companies that use agile and lean approaches, because of the complex pre‐planning activities required. In this paper, traditional portfolio management tools and methods that have been conventionally used in industry and presented in literature are reviewed. Findings concerning their use in agile and lean software companies are investigated, on the basis of the literature review and semi‐structured interviews conducted in 7 agile and lean software companies in Finland. The findings indicate that the studied companies do not use traditional portfolio management tools and methods in their entirety. The software companies adapted suitable components from traditional portfolio management tools and methods into their practices. They also apply new tools and methods to manage their portfolios of offerings, to cope with the dynamics required by agile and lean methods. The companies' emphasis is on using tools to facilitate immediate feedback from customers, to assess the value of offerings in their portfolio. The results showed a growing interest in using Kanban at the portfolio level to provide a visual overview of offerings. Abstract : Adopting agile and lean in software industry has brought challenges in the management of companies' portfolios. Our findings show that agile and lean software companies adapt to minimal use of traditional portfolio management tools and methods. The emphasis is on using tools that facilitate immediate feedback from customers, in order to assess the value of offerings in their portfolio. Additionally, software companies are increasingly adopting Kanban for portfolio management to visualize offerings and balance demand with capability during offerings development.